Investigating Postcolonial Feminism in Amitav Ghosh’s Novel Sea of Poppies (2008) - Messelem , Maroua; Bakhouche, Salah (University of Ammar Theledji -Laghouat, 2020)
The present study is an attempt to investigate the manifestations of Postcolonial feminism during the nineteenth century through the literary work of Amitav Ghosh‟s novel Sea of Poppies (2008). It draws connection between colonialism and the patriarchy society that oppresses women. The study states the problem of patriarchy and colonialism in the life of women. The importance of this research lays in the significant attention of postcolonial feminism in the literary criticism and also in the nascence of Amitav Ghosh‟s novel Sea of Poppies (2008). The fundamental aim of this study is to analyze the aspects Postcolonial feminism in the novel through following qualitative approach to offer an exploratory research that analyses and interprets the case of study Sea of Poppies (2008). The overall structure of this research takes the form of three chapters: The first chapter provides a brief overview of Postcolonial literature, than it draws a logical connection between Postcolonial and feminist theories and also between Amitav Ghosh‟s real life and his fiction. The second chapter offers postcolonial reading to the novel Sea of Poppies (2008).The final chapter draws upon the entire thesis, tying up the various theoretical and empirical standards used in the previous chapters in order to explore the way women live in patriarchy society under colonialism. The findings indicate that women have a passive role in the Indian society. Also, the subject of the subaltern as an Indian woman is struggling against patriarchy and colonialism in the same time. Moreover, Patriarchy system can not imprison women for their entire life unless they took revolutionary attitudes.